Cryptotanshinone Attenuates Airway Remodeling by Inhibiting Crosstalk Between Tumor Necrosis Factor-Like Weak Inducer of Apoptosis and Transforming Growth Factor Beta 1 Signaling Pathways in Asthma - Wang, Chongyang; Zheng, Mingyu; Choi, Yunho; Jiang, Jingzhi; Li, Li; Li, Junfeng; Xu, Chang; Xian, Zhemin; Li, Yan; Piao, Hongmei; Li, Liangchang; Yan, Guanghai (Frontiers in Pharmacology, 2019)
The study is to investigate the effect of cryptotanshinone (CTS) on airway remodeling and the possible mechanism. Male BALB/c mice were pretreated with CTS or dexamethasone 30 min before nebulized inhalation of OVA. CTS significantly inhibited OVA-induced increases of eosinophils and neutrophils infiltration of bronchoalveolar lavage fluids (BALFs), reduced airway resistance in asthmatic mice, decreased the accumulation of inflammatory cells, the hyperplasia of goblet cells and the deposition of collagen in asthmatic mice lung tissue, as well as markedly attenuated the leakage of inflammatory cells and the level of OVA-specific IgE in BALFs. CTS also inhibited the expressions of α-SMA, TWEAK, Fn14, TGF-β1, Smad4 and phosphorylation of Smad2/3 and STAT3 (Tyr705). In comparison to TWEAK inhibitor or TWEAK siRNA, which were used to inhibit TWEAK/STAT3 signaling pathways, CTS caused a similar effect as them on airway remodeling. Additionally, CTS also played a similar role as the TGF-β1 inhibitor or TGF-β1 siRNA in TGF-β1/STAT3 signaling pathways in airway remodeling. The anti-inflammatory effects of CTS against OVA-induced airway remodeling may be through inhibiting STAT3, which further suppresses TWEAK and TGF-β1 signaling cross talk in asthma. CTS may be a promising therapeutic reagent for asthma treatment.